Spectral characteristics of active medium for tunable dye laser - Maslov, V.V. (Functional Materials, 2012)
Spectral and fluorescent characteristics of mixtures of two couples of laser dyes for the red region have been studied with the purpose of tuning range broadening. Energy transfer of the monochromatic pumping from donor to acceptor was used in the first pair. The second couple of the dyes had the absorption spectra in the close spectral regions near wavelength of pumping, but its fluorescence spectra were characterized by essentially different Stokes shifts. As a result, the fluorescent band of the dye mixture expanded. The appreciable influence of solvents on fluorescence and laser characteristics of the second couple of the dyes has been revealed. Measuring of quantum yield of the dyes showed for one of them — DCM this characteristic was the largest in aprotic bipolar dimethylsulfoxide and the smallest in proton-donating methanol. The continuous tuning of laser radiation from 575 nm to 734 nm has been fulfilled under laser pumping of the selected dyes and its mixtures.